2004
DOI: 10.1126/science.1102755
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Sensor for siRNA Asymmetry

Abstract: To act as guides in the RNA interference (RNAi) pathway, small interfering RNAs (siRNAs) must be unwound into their component strands, then assembled with proteins to form the RNA-induced silencing complex (RISC), which catalyzes target messenger RNA cleavage. Thermodynamic differences in the base-pairing stabilities of the 5' ends of the two approximately 21-nucleotide siRNA strands determine which siRNA strand is assembled into the RISC. We show that in Drosophila, the orientation of the Dicer-2/R2D2 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
527
2
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 539 publications
(562 citation statements)
references
References 22 publications
19
527
2
8
Order By: Relevance
“…Dicer not only generates short-lived double-stranded siRNA and miRNA intermediates but also participates in the downstream process that lead to the selection of one of the strands, the guide strand of an siRNA, and participates in its incorporation into an Argonaute. The combination of genetic and biochemical approaches in fly identified the RISC loading complex (RLC) that activates and transfers one strand of an siRNA onto the fly Ago2 Lee et al, 2004;Pham et al, 2004;Tomari et al, 2004b). RLC contains at least Dicer-2, one of the two fly Dicers that predominantly process long dsRNAs and bind to siRNAs, and its dsRNA-binding interactor R2D2 (Tomari et al, 2004b).…”
Section: Risc Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dicer not only generates short-lived double-stranded siRNA and miRNA intermediates but also participates in the downstream process that lead to the selection of one of the strands, the guide strand of an siRNA, and participates in its incorporation into an Argonaute. The combination of genetic and biochemical approaches in fly identified the RISC loading complex (RLC) that activates and transfers one strand of an siRNA onto the fly Ago2 Lee et al, 2004;Pham et al, 2004;Tomari et al, 2004b). RLC contains at least Dicer-2, one of the two fly Dicers that predominantly process long dsRNAs and bind to siRNAs, and its dsRNA-binding interactor R2D2 (Tomari et al, 2004b).…”
Section: Risc Formationmentioning
confidence: 99%
“…The combination of genetic and biochemical approaches in fly identified the RISC loading complex (RLC) that activates and transfers one strand of an siRNA onto the fly Ago2 Lee et al, 2004;Pham et al, 2004;Tomari et al, 2004b). RLC contains at least Dicer-2, one of the two fly Dicers that predominantly process long dsRNAs and bind to siRNAs, and its dsRNA-binding interactor R2D2 (Tomari et al, 2004b). The key determinant in strand selection and unwinding is the thermodynamic difference between the two 5 0 ends of an siRNA (Khvorova et al, 2003;Schwarz et al, 2003).…”
Section: Risc Formationmentioning
confidence: 99%
“…How the asymmetry is achieved mechanistically is not known, although it likely involves differential binding to, and then differential retention of, the two individual RNA strands by Dicer and its associating proteins (Tomari et al, 2004). At the RNA sequence level, it appears that the strand with the less stable hydrogen bonding at its 5 0 end within the original duplex is selectively stabilized and becomes the mature miRNA, whereas its complementary strand is lost (Khvorova et al, 2003;Schwarz et al, 2003).…”
Section: Dicer Cleavage Of Pre-mirnasmentioning
confidence: 99%
“…Subsequent studies revealed that this potential asymmetric sensing mechanism was possible for mature siRNA and for siRNA processed from long dsRNA precursors [45]. Using radiolabeled siRNA and native gel electrophoresis, Drosophila Dicer-2 and R2D2 were identified in an RISC loading complex required for the formation of RISC [19,44]. These studies outline a role for Dicer and dsRBP in generating, loading and activating RISC in an asymmetric manner.…”
Section: Risc Assembly and Activationmentioning
confidence: 93%
“…Tomari et al [44] initiated studies aimed at elucidating the interaction of Dicer-2 and R2D2 with siRNA. Crosslinking experiments indicated a possible role for R2D2 in sensing thermodynamic siRNA structure.…”
Section: Risc Assembly and Activationmentioning
confidence: 99%